mTOR: A Potential Therapeutic Target in Osteoarthritis? - Pal, Bandna (Drugs R D, 2015)
Osteoarthritis (OA) is a chronic degenerative joint disease characterized by the progressive loss of articular cartilage, remodeling of the subchondral bone, and synovial inflammation. Mammalian target of rapamycin (mTOR) is a serine/threonine protein kinase that controls critical cellular processes such as growth, proliferation, and protein synthesis. Recent studies suggest that mTOR plays a vital role in cartilage growth and development and in altering the articular cartilage homeostasis as well as contributing to the process of cartilage degeneration associated with OA. Both pharmacological inhibition and genetic deletion of mTOR have been shown to reduce the severity of OA in preclinical mouse models. In this review article, we discuss the roles of mTOR in cartilage development, in maintaining articular cartilage homeostasis, and its potential as an OA therapeutic target.